Health seeking behavior regarding men’s health disorders among government servants in Kuantan: prevalence study towards healthy ummah - Md Isa, Muhammad Lokman; Mat Yusof, Afzan (2016)
As age deteriorates, most of body system will deteriorates as well, same goes to reproductive health. Wide gap between the prevalence of reproductive health disorders and rates of treatment seeking among middle aged and older men are still low compared to other chronic disease. In Islam, seeking medical treatment for the cure of diseases is part of the prophet’s tradition and in a saheeh hadith that the prophet (s.a.w.) said the following:“For every disease there is a medicine, and if that medicine is applied to the disease, he will recover by Allah’s Leave.” Therefore the aim of this study is to identify health seeking behavior among men regarding men’s health disorders in Kuantan. 157 respondents are involved in this study and the data was collected using self-administered questionnaire modified from a valid and reliable measure. The results showed that 68.2% of the respondents (n=107) have high attitude in seeking for health regarding men’s health while for the rest of the respondents (n=50, 31.8%) have low attitude in seeking for health. Service factor perceived the highest among the other two factors which are cultural and economic factor. This study showed that men’s health that includes reproductive disorders has always been taken lightly by the community itself. Lack of awareness regarding men’s health issue causes men to ignore the importance of health screening towards men’s health. This phenomenon should be improved in order to produce a healthy community for better ummah.